2022
DOI: 10.3390/curroncol29060342
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Predictive Relevance of Tumor-Infiltrating Lymphocytes in Squamous Cell Head–Neck Cancer Patients Treated with Radical Radiotherapy/Chemo-Radiotherapy

Abstract: Microenvironmental conditions control the entrance and thriving of cytotoxic lymphocytes in tumors, allowing or preventing immune-mediated cancer cell death. We investigated the role of tumor-infiltrating lymphocyte (TIL) density in the outcome of radiotherapy in a series of squamous cell head–neck tumors (HNSCC). Moreover, we assessed the link between markers of hypoxia and TIL density. One-hundred twenty-one patients with HNSCC treated prospectively with radical radiotherapy/chemo-radiotherapy were analyzed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
3
5
0
Order By: Relevance
“…An important finding was also the association of HIF1α with low infiltration of PCs with TILs in accordance with previous studies in breast and head–neck cancer [ 27 , 28 ]. A hypoxic and acidic TME provides a functional barrier against cytotoxic lymphocytes, blocking their proliferation and cytotoxic activity, and furthermore, promotes regulatory T-cell and monocyte prevalence [ 6 10 ].…”
Section: Discussionsupporting
confidence: 91%
“…An important finding was also the association of HIF1α with low infiltration of PCs with TILs in accordance with previous studies in breast and head–neck cancer [ 27 , 28 ]. A hypoxic and acidic TME provides a functional barrier against cytotoxic lymphocytes, blocking their proliferation and cytotoxic activity, and furthermore, promotes regulatory T-cell and monocyte prevalence [ 6 10 ].…”
Section: Discussionsupporting
confidence: 91%
“…Many studies support the importance of quantitative and qualitative characteristics of the immune infiltrate in the prognosis of patients. In particular, tumor-infiltrating lymphocytes (TILs) and tertiary lymphoid structures (TLSs) are found to have an impact in patient’s prognosis in a variety of solid tumors, including head–neck carcinomas [ 11 , 12 , 16 , 19 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-infiltrating lymphocytes (TILs) are known to affect the prognosis of HN cancer patients [ 11 ], as well as the response to RT and chemotherapy [ 12 ]. As a tumor grows in a microenvironment with abnormal dysfunctional vasculature and poor oxygen availability, cancer cells use anaerobic glycolysis to cover their metabolism needs.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a study on head and neck cancer observed that the frequency of infiltrated TILs into the tumor site increased following radiotherapy and chemo/radiotherapy. Furthermore, this investigation reported that the expression of HIF-α as a hypoxia indicator decreased following the combination therapy ( 203 ).…”
Section: Combination Of Tils With Other Anti-cancer Therapiesmentioning
confidence: 97%